Network optimization and reconstruction for 5G - Lingyi KONG (Dianxin kexue)
In June 2019,the Ministry of Industry and Information Technology officially issued a 5G commercial license,which accelerated the deployment of telecom operator’s network of 5G.NSA networking is a good choice to deploy 5G networks in the early stage,and SA networking is the target architecture of 5G networks.Based on the network existing,how to smooth evolution to 5G is a problem to be considered.The architecture of 4G networks was introduced briefly,the return bearer network was optimized to meet the bandwidth requirement in the early stage of 5G development,Through NFV technology the EPC was reconstructed based on CUPS architecture to support network evolution better.Finally,the inter working architecture of 4G/5G was introduced,the deployment and evolution scheme for SA network was analyzed,which provides reference for the construction of 5G core network.